A transshipment-type model for the optimal allocation of foreign currencies in multinational corporations - Holger Hinz (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1987)
Starting in the late 1970's the attempt to rationalize multinational corporations' (MNCs) short-term liquid funds management led to the development and implementation of so-called "Netting Systems": In order to reduce the costs associated with transferring inter-affiliate payments, the idea behind these systems is to net out payables and receivables so that only this netted amount needs be transferred. Depending upon the MNCs' internal payments structure there are two possible ways of determining these fund flows: In case affiliates just sell back and forth to each other, a bilateral netting approach will suffice. Generally, though, more complex interdependencies among MNCs'-subsidiaries call for a multilateral netting system to be presented here. While scientific publications on international cash management problems have brought up applications of a great variety of methodological approaches (1), in my opinion the problem outlined above has proven to be highly suggestive to mathematical programming techniques. Starting out I will therefore describe a classical transportation-type approach (chapter 2), then develop a modified linear program (LP) in chapter 3 along with a numerical example (chapter 4), and finally draw some conclusions in chapter 5.
Keywords: 650; Multinationales Unternehmen; Währungsmanagement